Detection of aneuploidy from single fetal nucleated red blood cells using whole genome sequencing. (16th October 2014) - Hua, Rui; Barrett, Angela N.; Tan, Tuan Zea; Huang, Zhouwei; Mahyuddin, Aniza Puteri; Ponnusamy, Sukumar; Sandhu, Jaspal Singh; Ho, Sherry S. Y.; Chan, Jerry K. Y.; Chong, Samuel; Quan, Song; Choolani, Mahesh
Abstract Objective The objective of the study was to detect aneuploidy in single fetal nucleated red blood cells (FNRBCs) from placental villi using whole genome amplification (WGA) and next generation sequencing. Methods Three single FNRBCs per sample were manually picked from villi collected from ten women undergoing elective first‐trimester termination of pregnancy, and one or two cells were picked from each of four aneuploid chorionic villus samples. Following WGA and addition of adaptor and index sequences, samples were sequenced on the Illumina MiSeq. Leading and trailing 15 bases were trimmed, and reads were aligned to the human reference genome. Z‐scores were calculated to determine deviation of the mean of the test from reference samples, with a score of 3 used as the threshold for classification of a particular chromosome as trisomic. Results We successfully made correct diagnoses from ten single cells isolated from villi from two cases of trisomy 21 (one case from a single cell and one from two cells), two cases of trisomy 18 (two cells each), and a case of trisomy 15 (three cells). Conclusion With their faithful representation of fetal genome, diagnosis using single FNRBCs provides a definitive result compared with non‐invasive prenatal testing using cell‐free fetal DNA, and is a safer alternative to invasive amniocentesis. © 2014 John Wiley & Sons, Ltd.